Steering innovations towards a green economy: Understanding government intervention. (1st November 2016) - Droste, N.; Hansjürgens, B.; Kuikman, P.; Otter, N.; Antikainen, R.; Leskinen, P.; Pitkänen, K.; Saikku, L.; Loiseau, E.; Thomsen, M.
Abstract: In this paper we analyse institutional conditions facilitating the transition towards a green economy by encouraging investment in the enhancement of natural capital and social equity, focussing especially on government interventions. Presenting a conceptual institutional model how innovation generally occurs, we depict system levels that can be influenced by government interventions to facilitate societal innovations towards a green economy. We hypothesize that the transition to a green economy is about extending the possibility frontier outwards towards a greener economy while at the same time limiting the "action space" at the brown economy end; a normative evaluation framework is presented to assess transitions correspondingly. We elaborate on the emerging lessons for governance by examining evidence from five selected European case studies, and provide a non-exhaustive list of impacts that government intervention may have on the action spaces available at different system levels. Highlights: We propose a systemic innovation approach to explain paths towards a green economy. We show how green economy transitions are shaped by governance intervention. We provide case study evidence from five European countries.